Understanding Wetland Environmental Risk Mitigation Communication Strategy: A case study in Banjarmasin - Astuty, Sri; Yuwanto, Yuwanto; Alfirdaus, Laila Kholid; Akhmad, Bachruddin Ali (International Journal Labs, 2023)
The environmental problems of wetlands in Indonesia, especially in Kalimantan, are not only problems of land fires, haze, floods, but can also be in the form of collapse of buildings due to the contour of swampland and the use of river channels with various uses both for community life, transportation facilities, and river channels as part of tourist destinations. The purpose of this study is to explain the problem of phenomena that often occur in wetlands for tourism activities. Qualitative research methods with case studies, data collection techniques are carried out by collecting various news about motorboat accidents, observations, interviews, and documentation of river crossing tours from social media. The results showed that mitigation communication to prevent accidents in river channel tourism activities has three components that should be jointly responsible, namely the government, river crossing tourism managers, and river crossing visitor communities. Three components are not partially but comprehensively responsible for overcoming problems with risk mitigation. The river is part of the local wisdom of the people in Kalimantan, by utilizing the existing potential to maximize the increase in tourism objects based on comfort and safety.